Isolated dextrocardia and rheumatoid arthritis with mitral stenosis with pulmonary hypertension with atrial fibrillation: A rare association (Indian Journal of Case Reports, 2024)
This case presents a rare occurrence of rheumatoid arthritis (RA) in a 50-year-old woman with concurrent mitral valvular disease and dextrocardia. Diagnosed with seropositive RA 5 years earlier, the patient exhibited fever, cough, and progressive dyspnea. Clinical examination revealed irregular tachycardia, elevated jugular venous pressure, and signs of heart failure. Laboratory results confirmed seropositive RA, anemia, and elevated inflammatory markers. Electrocardiogram and echocardiogram indicated dextrocardia, atrial fibrillation, and moderate mitral stenosis. This case highlights the unusual association of RA with valvular heart disease and the added complexity of dextrocardia. Recognizing diverse cardiac manifestations in RA is crucial, contributing to the growing evidence linking autoimmune disorders to cardiovascular complications. Further research is essential to understand the intricate relationship between RA and unique cardiac abnormalities.